2011
DOI: 10.1161/hypertensionaha.111.170910
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion by Myocardial Contrast Echocardiography and Endothelial Dysfunction in Obstructive Sleep Apnea

Abstract: Abstract-Obstructive sleep apnea is associated with increased cardiovascular morbidity and mortality. We investigated myocardial perfusion using real-time quantitative myocardial contrast echocardiography with concurrent assessment of macrovascular and microvascular endothelial dysfunction in normotensive subjects with moderate-to-severe obstructive sleep apnea, who were compared with hypertensive and healthy subjects, as well as the impact of continuous positive airway pressure treatment on obstructive sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 46 publications
(51 reference statements)
7
40
0
Order By: Relevance
“…In subjects with OSA, but otherwise healthy, endothelium-dependent vasodilatation is impaired, 65 and, in randomized trials, treating OSA by CPAP improved both endothelium-dependent and/or -independent vasodilatation without reducing plasma biomarkers of inflammation. 65 Butt and colleagues 68 recently reported that otherwise healthy patients with OSA had impaired myocardial perfusion that improved with CPAP. Enhanced apoptosis of endothelial cells and fewer circulating endothelial progenitor cells in OSA patients may contribute to these processes.…”
Section: Oxidative Stress Inflammation and Endothelial Dysfunctionmentioning
confidence: 99%
“…In subjects with OSA, but otherwise healthy, endothelium-dependent vasodilatation is impaired, 65 and, in randomized trials, treating OSA by CPAP improved both endothelium-dependent and/or -independent vasodilatation without reducing plasma biomarkers of inflammation. 65 Butt and colleagues 68 recently reported that otherwise healthy patients with OSA had impaired myocardial perfusion that improved with CPAP. Enhanced apoptosis of endothelial cells and fewer circulating endothelial progenitor cells in OSA patients may contribute to these processes.…”
Section: Oxidative Stress Inflammation and Endothelial Dysfunctionmentioning
confidence: 99%
“…However, interpretation of current data are limited by the cross-sectional design of certain studies, 20 and the presence of a wide range of confounding factors such as existing comorbidities and other cardiovascular risk mediators. To reduce the possibility of confounding, Butt et al 21 recently looked at normostensive patients with moderate-severe OSA (with no apparent cardiovascular disease), and performed myocardial perfusion imaging as compared with 2 sets of matched controls without OSA (hypertensive patients and healthy subjects). Patients with OSA were found to have significant abnormalities in myocardial perfusion, as well as attenuated brachial artery reactivity when compared with healthy controls, thus lending support to the hypothesis regarding endothelial dysfunction in OSA.…”
Section: The Pathogenesis Of Osa-related Cardiovascular Eventsmentioning
confidence: 99%
“…9 The critical role of chronic intermittent hypoxia (CIH) exposure in the development of cardiovascular changes induced by OSA is supported not only by clinical studies reporting the beneficial cardiovascular effects of the treatment of OSA patients with continuous positive airway pressure [10][11][12][13] but also by experimental data showing that animals exposed to CIH develop sustained hypertension, 14 an effect prevented by previous denervation of peripheral chemoreceptors. 15 In this brief review, we discuss recent data about the possible mechanisms underpinning the hypertension induced by CIH exposure, with focus on the development of the sympathetic overactivity that is associated with this pathophysiological condition.…”
mentioning
confidence: 99%